Genetic analysis of stifle arthrosis in Swedish boxer dogs - Wistedt, Anna (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2006)
Stifle problems in Boxer dogs have been a major issue in discussions in Swedish boxer breeding circles for a long time. Since 1997, the Swedish Kennel Club (SKC) has a ge-netic health programme for boxers to reduce the number of dogs affected by stifle arthrosis.